Firm Size and Entrepreneurial Characteristics : Evidence from the SME Sector in Argentina - de Jorge Moreno, Justo; Laborda Castillo, Leopoldo; de Zuani Masere, Elio (2012)
This study investigates the determinants of firm size. Data was collected in face-to-face structured-questionnaire interviews of 1314 firm founders from 14 counties in Argentina. Quantile regression was used as a more suitable methodology to measure the determinants of firm size. Our results show that the main sets of explanatory variables related to founder characteristics (age, experience, education, and vocation) provide a full explanation of firm size. We have also found evidence that a high degree strategic planning and a better competitive position are positively related to firm size as well. Finally, environmental factors were less representative.